Engineering of a metagenome derived lipase toward thermal tolerance: Effect of asparagine to lysine mutation on the protein surface - Sharma, Pushpender K. (Elsevier B.V., 2012)
A highly thermostable mutant lipase was generated and characterized. Mutant enzyme demonstrated 144 fold enhanced thermostability over the wild type enzyme at 60°C. Interestingly, the overall catalytic efficiency (k cat/K m) of mutant was also enhanced (~20 folds). Circular dichroism spectroscopy, studied as function of temperature, demonstrated that the mutant lipase retained its secondary structure up to 70-80°C, whereas wild type protein structure was completely distorted above 35°C. Additionally, the intrinsic tryptophan fluorescence (a probe for the tertiary structure) also displayed difference in the conformation of two enzymes during temperature dependent unfolding. Furthermore, mutation N355K resulted in extensive H-bonding (Lys355 HZ1OE2 Glu284) with a distance 2.44Å. In contrast to this, Wt enzyme has not shown such H-bonding interaction.
Only IISERM authors are available in the record.
Keywords: asparagine; DNA; hydrogen